First report of Enterobacter sp. causing bacterial wilt on patchouli in Aceh, Indonesia - ZULFADLI ZULFADLI; NURAINUN INTAN WASISTHA; HARTATI OKTARINA; KHAIRAN KHAIRAN; RINA SRIWATI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Zulfadli, Wasistha NI, Oktarina H, Khairan, Sriwati R. 2023. First report of Enterobacter sp. causing bacterial wilt on patchouli in Aceh, Indonesia. Biodiversitas 24: 3814-3820. Patchouli (Pogostemon cablin Benth), is an essential commodity in Indonesia, with Aceh Jaya being one of its main producing regions. Several incidences of wilt disease symptoms have been reported in patchouli plantations in Ranto Sabon, Sampoianet Sub-district, Aceh Jaya District. This study aimed to isolate and identified the bacterial pathogen responsible for wilt disease in patchouli in Aceh Jaya. Various tests, including morphology characterization and molecular characteristics using 16s PCR primer, hypersensitive test, and pathogenicity test were conducted to identify the cause of disease. The isolation result revealed that Enterobacter sp. was responsible for invading the patchouli plant. Further testing was carried out on various culture media including Nutrient Broth, Tryptic Soy, Kings B, Sulfide Indole Motility, Sucrose Potato Agar, and Yeast Potato Agar. The highest colony density was found in Tryptic Soy media (2.002) after 120 hours of inoculation. The results of hypersensitivity and pathogenicity tests showed that Enterobacter sp. caused symptoms similar to those of natural infection. Among all the media, Sucrose Potato Agar media had the fastest incubation period, with 7 and 48 days after inoculation. Therefore, this is the first study to report the presence of Enterobacter sp. associated with bacterial wilt in patchouli in Aceh.